Integrating Productive Waqf and Green Economy: Implementation in Empowering the Economy of Coastal Communities in The Malacca Strait - Nurmatias, Faizal; Akbar, Muhammad Rizal; Firdaus , Muhamad Farid; Adawiyah , Robiyatul; Syahfawi, Syahfawi; Walian, Armansyah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose -This study aims to explore the integration of productive waqf and green economy as a strategic model for empowering coastal communities in the Straits of Malacca. The focus lies on how waqf, as an Islamic social finance instrument, can support sustainable development by aligning with the principles of resource efficiency, low carbon practices, and social inclusiveness. Method - The research employs a library research design with a qualitative descriptive-analytical approach. Data were collected from books, peer-reviewed journals, official reports from institutions such as BWI, UNEP, and UNDP, as well as fatwas from DSN-MUI and relevant academic studies. The analysis technique used content analysis, thematic comparison, and normative interpretation to examine the synergy between productive waqf and green economy in coastal community development. Findings - The study reveals that productive waqf has strong potential to be integrated into green economy initiatives, such as financing renewable energy projects in coastal areas, supporting sustainable aquaculture, establishing halal-based eco-tourism, and developing waste management for marine products. This integration not only contributes to economic resilience but also preserves marine ecosystems and aligns with maqāṣid al-sharī‘ah in safeguarding life, wealth, and the environment. Furthermore, the Straits of Malacca context highlights the strategic urgency of such a model due to its economic potential and ecological vulnerability. Implications - Theoretically, this research expands the discourse on waqf by situating it within the framework of sustainable development and global SDGs. Practically, it offers recommendations for local governments, the Indonesian Waqf Board (BWI), and nazir to adopt green economy-oriented approaches in managing waqf assets. The study also suggests further empirical research on the implementation of productive waqf projects in Indonesian coastal regions to validate and enrich the conceptual framework proposed